Implementation of the Role of Public Prosecutors as Dominus Litis in General Criminal Cases According to the Provisions of Law Number 20 of 2025 Concerning the Criminal Procedure Code - Muhammad Rizki Mahyuzar; Faisal Riza (Fox Justi : Jurnal Ilmu Hukum, 2026)
This study aims to examine the implementation of the Public Prosecutor's role as dominus litis in the handling of general criminal cases under the provisions of Law Number 20 of 2025 concerning the Indonesian Criminal Procedure Code (KUHAP). The dominus litis concept positions the Public Prosecutor not merely as a party who prosecutes cases in court but as the central controller of the entire criminal justice process, spanning from the investigation, inquiry, prosecution, trial, to the execution of court decisions. This research employs a normative-analytical approach, reviewing statutory regulations, legal doctrines, and criminal law theories, including the crime control and due process models, principles of the rule of law, mechanisms of checks and balances, and human rights protection. The study finds that KUHAP 2025 reinforces the Public Prosecutor's position as the central authority responsible for the continuity and consistency of all procedural stages. The implementation of dominus litis effectively balances the need for efficient law enforcement with the protection of the rights of suspects and defendants, thus ensuring a criminal justice system that is accountable, integrated, and just.